Probability of Deck Wetness and Bottom Slamming due to Height and Wave Directions on Klotok Boat - Andi Mursid Nugraha Arifuddin; Silvia Salsa Putri; Muhammad Uswah Pawara; Harlian Kustiwangsa; Jusma Wahidah; Fernanda Wahyu Pratama; Cindy Lionita Agusty (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Sailing safety is an important aspect that must be considered to ensure the safety of the crew and passengers. One aspect that affects sailing safety is the probability of deck wetness and bottom slamming on each ship. A research object is a traditional wooden boat hull operating on the Penjam - Balikpapan route that transports passengers and vehicles. The aim is to provide information regarding wave conditions that support the safe operation of klotok ships. In this study, the variations in wave arrival directions used are 45°, 90°, 135° and 180° with a ship speed of 8 knots, and variations in wave height are based on the sea state approach, namely sea state 1 (0.488 m), sea state 2 (1.006 m), sea state 3 (1.433 m), and sea state 4 (2.012 m). Furthermore, the m0 value is obtained as an important component to measure the occurrence of deck wetness and bottom slamming through an approximation formula and validated with the NORDFORSK 1987 criteria. The results of the study indicate that the highest probability value of deck wetness occurs in the direction of wave arrival 180° with a wave height at sea state 4 (2.102 m). While the highest probability value of bottom slamming occurs in 2 variations of wave arrival direction, namely 135° and 1800. The wave height that must be considered in the direction of wave arrival 135° is 1.433 m and 2.012 m. Meanwhile, if the direction of wave arrival is 180°, the wave height that must be considered is 1.006 m, 1.433 m, and 2.012 m. With initial information on the potential for deck wetness and bottom slamming, it can be recommended that ships will tend to sail safely if waves arrive at 450 and 900 degrees, while immediately avoiding ship movements in the direction of waves at 1350 and 1800 degrees, especially at extreme wave heights. This condition will occur if the gravity concentration position is in the forecastle position. Meanwhile, if the gravity concentration position is at the stern, the passenger room and vehicle deck show a probability value that tends to be safe.